1998
DOI: 10.1046/j.1365-313x.1998.00061.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of plant viral systemic infection by non‐toxic concentrations of cadmium

Abstract: SummaryHeavy metals, such as cadmium, have a significant impact on plant physiology. However, their potential effect on plant-pathogen interaction, an important biological process, has not been examined. This study shows that exposure of tobacco plants to non-toxic concentrations of cadmium completely blocked viral disease caused by turnip vein clearing virus. Cadmium-mediated viral protection was due to inhibition of the systemic movement of the virus, i.e. its spread from the inoculated into uninoculated lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0
14

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 37 publications
4
56
0
14
Order By: Relevance
“…The systemic movement of the silencing signal takes days and typically moves from leaves (photosynthetic source) to roots and growing points (sucrose sinks) ; this flow is characteristic of phloem (discussed in (Turgeon and Wolf, 2009;De Schepper et al, 2013)). Furthermore, phloem transport blocked by cadmium inhibits systemic silencing spread (Beclin et al, 1998;Ghoshroy et al, 1998). Later, it was also shown that phloem flow strongly influences the systemic spread of silencing in Nicotiana benthamiana and that the direction of systemic spread of silencing from inducer to sensor can be manipulated by altering sink/source relations in the plant (Tournier et al, 2006).…”
Section: Efsa Supporting Publication 2017:en-1246mentioning
confidence: 99%
“…The systemic movement of the silencing signal takes days and typically moves from leaves (photosynthetic source) to roots and growing points (sucrose sinks) ; this flow is characteristic of phloem (discussed in (Turgeon and Wolf, 2009;De Schepper et al, 2013)). Furthermore, phloem transport blocked by cadmium inhibits systemic silencing spread (Beclin et al, 1998;Ghoshroy et al, 1998). Later, it was also shown that phloem flow strongly influences the systemic spread of silencing in Nicotiana benthamiana and that the direction of systemic spread of silencing from inducer to sensor can be manipulated by altering sink/source relations in the plant (Tournier et al, 2006).…”
Section: Efsa Supporting Publication 2017:en-1246mentioning
confidence: 99%
“…How does this effect of overexpressed calreticulin influence viral infection and cell-to-cell movement? To address this question, we used a coat protein (CP) assay in which TMV presence is detected by appearance of the viral CP within the inoculated tissues (Lartey et al, 1997;Ghoshroy et al, 1998;Chen et al, 2000;Waigmann et al, 2000). N. benthamiana leaves were inoculated with TMV, and the appearance of TMV CP due to the cell-to-cell movement of the virus was assayed in leaf areas distal to the inoculation site using western-blot analysis and anti-TMV CP antibodies.…”
Section: Calreticulin-tmv Mp Interaction In Vivo and In Vitromentioning
confidence: 99%
“…The effects of other stress factors on virus infection have been also investigated (Ghoshroy et al, 1998). Favourable side effects of some herbicides and plant extracts, as virus inhibitors, have been discovered (Schuster, 1972(Schuster, , 1982Horvá th and Hunyadi, 1973;Rao et al, 1994;Kazinczi et al, 2002Kazinczi et al, , 2003Kazinczi et al, , 2005a.…”
Section: Introductionmentioning
confidence: 99%